Evaluation of sample rejection rate in clinical biochemistry laboratory before and after implementation of six-sigma methodology - Nandita Maini Jindal; Bajwa, Navjot Kaur; Bansal, Ekta; Ghosh, Abhra (Asian Journal of Medical Sciences, 2023)
Background: In pre-analytical phase of Clinical Biochemistry Laboratory, sample rejection is a very frequent and important source of error. It affects the overall quality of laboratory services and patient care by increasing cost and turnaround time. It leads to test abandonment and causes inconvenience to patients and staff. Aims and Objectives: The aim of the study was to implement the define, measure, analyze, improve, and control (DMAIC) method of six-sigma to decrease the rate of sample rejection in Clinical Biochemistry Laboratory. Materials and Methods: In this prospective study, sample rejection rates were analyzed in a clinical Biochemistry Laboratory before and after implementation of DMAIC method of six-sigma. Baseline rejection rates were calculated for a year and classified based on cause of rejection and patient location. Current defects per million opportunities and six sigma values were calculated. This was followed by root cause analysis and implementation of corrective and preventive measures. Reanalysis of the baseline measures was done to observe the impact of these measures. Results: After implementation of DMAIC, the overall rejection rate fell from 1.07% to 0.49% with an increase in sigma value from 3.8 to 4.1. Conclusion: Six-sigma tool like DMAIC can be successfully implemented to improve sample rejection rates ultimately improving the quality of laboratory services in resource limited setting with minimal financial implications.